The influence of compensation, job stress, and job satisfaction on employee performance in the outsourcing company PT. Citra Bersama - Martono, Zwietsy; Rangkuti, Freddy (Jurnal Ekonomi Perusahaan, 2024)
This study aims to analyze the influence of job compensation, job stress, and job satisfaction on employee performance in the outsourcing company PT Citra Bersama. The research method used is a quantitative approach with survey techniques. The research population consists of 70 employees working in the company. The analysis results show that job compensation does not have a significant influence on employee performance in the outsourcing company PT Citra Bersama. Job stress does not have a significant relationship with employee performance. Job satisfaction has a significant influence on employee performance in the outsourcing company PT Citra Bersama. Factors such as recognition of performance, career development opportunities, and work-life balance are important in improving employee job satisfaction.